The Influence of Toxic Workplace Environment and Workload on Turnover Intention Through Work Stress at PT. Company X - Desak Komang Febrianita; Yeyen Komalasari; Budi Santoso; Gillbert Nainggolan (Maneggio, 2025)
This study examines the influence of toxic workplace environment and workload on turnover intention, with job stress acting as the mediating variable. The findings reveal that both toxic workplace environment and workload significantly increase employees’ job stress, which in turn contributes to higher turnover intention. The results also indicate that job stress significantly mediates the relationship between toxic workplace environment and turnover intention, as well as the relationship between workload and turnover intention. The indirect effects through job stress were found to be stronger than the direct effects. Overall, this research highlights the critical role of psychological stress in linking negative workplace conditions and job demands to employees’ intention to leave the organization. The study suggests that organizations should improve workplace culture and manage workload distribution to reduce job stress and turnover intention.